primer problema 2x² + 3 ≤ 7x
(x-3)(x-½)≤0
½≤×≤3
x=1 x=2 x=3
Respuesta [½,3]
(x – 2)² – 2(x² + 2) ≤ 0
x (x +4) ≥0
-x(x+4)≤0
-x²-4x≤0
x=0 x≤4
Respuesta
[0,∞) (-∞,-4]
6x² – 11x + 3 ≥ 0
6x² + 3=11x
(x3/2)(x-1/3)≥0
(2x-3)(3x-1)≥0
x≥3/2 x≤1/3
[3/2,∞) (-∞1/3]
espero te sirva
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
primer problema 2x² + 3 ≤ 7x
(x-3)(x-½)≤0
½≤×≤3
x=1 x=2 x=3
Respuesta [½,3]
(x – 2)² – 2(x² + 2) ≤ 0
x (x +4) ≥0
-x(x+4)≤0
-x²-4x≤0
x=0 x≤4
Respuesta
[0,∞) (-∞,-4]
6x² – 11x + 3 ≥ 0
6x² + 3=11x
(x3/2)(x-1/3)≥0
(2x-3)(3x-1)≥0
x≥3/2 x≤1/3
[3/2,∞) (-∞1/3]
espero te sirva
= 2x² + 3 ≤ 7x ; 2x² + 3 ≥ -7x
= 2x² -7x + 3 ≤ 0 ; 2x² + 7x + 3 ≥ 0
= 2 ( 2x² -7x + 3 ≤ 0 ) ; 2 ( 2x² + 7x + 3 ≥ 0 )
= 4x² - 14x + 6 ≤ 0 ; 4x² +14x + 6 ≥ 0
= ( 2x - 6 ) ( 2x - 1 ) ≤ 0 ; ( 2x + 6 ) ( 2x + 1 ) ≥ 0
= { 2x - 6 ≤ 0 & 2x - 1 ≥ 0 } ; { 2x +6 ≥ 0 & 2x +1 ≥ 0 }
{ 2x - 6 ≥ 0 & 2x - 1 ≤ 0 } ; { 2x +6 ≤ 0 & 2x +1 ≤ 0 }
= { x ≤ 6/2 & x ≥ 1/2 } ; { x ≥ - 6/2 & x ≥ - 1/2 }
{ x ≥ 6/2 & x ≤ 1/2 } ; { x ≤ - 6/2 & x ≤ - 1/2 }
= { x ≤ 3 & x ≥ 1/2 } ; { x ≥ - 3 & x ≥ - 1/2 }
{ x ≥ 3 & x ≤ 1/2 } ; { x ≤ - 3 & x ≤ - 1/2 }
Solución = [ 1/2 , 3 ]